1977
DOI: 10.3171/jns.1977.46.3.0304
|View full text |Cite
|
Sign up to set email alerts
|

Wave-form characteristics and spatial distribution of evoked spinal electrogram in man

Abstract: The evoked spinal electrogram (SEG) in man was recorded from the epidural space, applying the technique of continuous epidural block, and compared with cord dorsum potential (CDP) in wakeful rabbits. Wave-form characteristics of the evoked SEG'S activated by the segmental nerves were almost the same in both cervical and lumbar regions. Somatosensory evoked response from the scalp was clearly demonstrated by stimulation of both the tibial nerve and fifth toe skin, whereas the evoked SEG was produced only by sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
7

Year Published

1979
1979
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(16 citation statements)
references
References 24 publications
3
6
0
7
Order By: Relevance
“…Indeed, the amplitudes of the penile evoked responses are well correlated with the distance of the epidural recording site from conus medullaris judged by the amplitude of the first negative component of the tibial segmental cord responses [Ertekin, 1976, 19781. The shape of the penile cord potentials was similar to tibial cord potentials in a given subject except that all sequences of the evoked response were very small and the deep positive wave or P-wave following the first prominent negative sharp wave was less defined and smaller in amplitude than that of the tibial cord potential. This finding is compatible with our previous experience that the segmental cord potential is small with poorly defined late components as a response to the stimulation of a pure sensory cutaneous nerve, such as the sural nerve, compared to those recorded after the stimulation of a mixed nerve such as the tibial nerve [Ertekin, 1973[Ertekin, , 1976Shimoji et al, 1977;Ertekin et al, 1984;Cracco et al, 1980;Philips and Daube, 19801. The latencies of the penile segmental cord potentials were about 1-3 msec shorter than those that were evoked by stimulating the tibial nerve at the level of the popliteal fossa. On the other hand the distances between the stimulation and recording sites are not comparable, being about twice as long for the tibial cord potentials.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, the amplitudes of the penile evoked responses are well correlated with the distance of the epidural recording site from conus medullaris judged by the amplitude of the first negative component of the tibial segmental cord responses [Ertekin, 1976, 19781. The shape of the penile cord potentials was similar to tibial cord potentials in a given subject except that all sequences of the evoked response were very small and the deep positive wave or P-wave following the first prominent negative sharp wave was less defined and smaller in amplitude than that of the tibial cord potential. This finding is compatible with our previous experience that the segmental cord potential is small with poorly defined late components as a response to the stimulation of a pure sensory cutaneous nerve, such as the sural nerve, compared to those recorded after the stimulation of a mixed nerve such as the tibial nerve [Ertekin, 1973[Ertekin, , 1976Shimoji et al, 1977;Ertekin et al, 1984;Cracco et al, 1980;Philips and Daube, 19801. The latencies of the penile segmental cord potentials were about 1-3 msec shorter than those that were evoked by stimulating the tibial nerve at the level of the popliteal fossa. On the other hand the distances between the stimulation and recording sites are not comparable, being about twice as long for the tibial cord potentials.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is compatible with our previous experience that the segmental cord potential is small with poorly defined late components as a response to the stimulation of a pure sensory cutaneous nerve, such as the sural nerve, compared to those recorded after the stimulation of a mixed nerve such as the tibial nerve [Ertekin, 1973[Ertekin, , 1976Shimoji et al, 1977;Ertekin et al, 1984;Cracco et al, 1980;Philips and Daube, 19801.…”
Section: Discussionsupporting
confidence: 80%
“…1). The recording methods resembled those used in previous investigations (Shimoji et al, 1971(Shimoji et al, , 1977 on human CDP with in addition a weak epidural stimulation of the spinal cord. The subjects were placed in the lateral decubitus for fixation of the electrodes.…”
Section: Methodsmentioning
confidence: 97%
“…In addition, the slow potentials sometimes have proved difficult to record with a surface electrode (Shimoji et al, 1978). A simple, safe method of recording human CDP has been developed using an epidural catheter as a recording electrode (Shimoji et al, 1971), and its potential pattern has been shown to resemble that of CDP directly recorded from the cord surface in animals (Shimoji et al, 1976(Shimoji et al, , 1977. Here we report slow negative-positive potentials recorded from the posterior epidural space at the lumbar enlargement, elicited by volleys descending through the cord in normal man, while these potentials are absent in patients suffering from amyotrophic lateral sclerosis.…”
Section: Tractmentioning
confidence: 99%
“…It follows that the response recorded by C7-Sn upon stimulation of the upper lim'b (that is RII) is likely to be mainly (or exclusively) related to segmental events generated by dipoles which are horizontally oriented, as suggested by the maximal amplitude of the CDP in the anteroposterior axis on the horizontal plane. 13 We conclude that the electrophysiological events underlying RI cannot be identified with those responsible for RII. In this connection it seems of relevance that in spinal man RII is still present,'4 while only the initial portion of RI (that is N9 and NIl) can be recorded after a complete spinal cord lesion3 at C5.…”
Section: Discussionmentioning
confidence: 82%